Panchromatic Analysis for Nature of HIgh-z galaxies Tool (PANHIT). Issue Volume 15:Issue S341(2019) (November 2019) - Mawatari, Ken; Inoue, Akio K.; Yamanaka, Satoshi; Hashimoto, Takuya; Tamura, Yoichi
Abstract: We have developed a new SED fitting tool specialized for frontier redshift galaxies. It is a common case for high- z galaxies that the available data are restricted to rich optical to near-infrared photometry and few far-infrared (FIR) data deep enough to detect the faint object (e.g., HST /WFC3 + Spitzer /IRAC + ALMA). In such situation, one cannot perform a complicated modeling of dust emission in FIR regime. We then adopt simple treatment for the dust emission using empirical LIRG templates. Instead, we adopt a sophisticated and physically motivated modeling for stellar and nebular emission parts in rest-frame UV-to-optical regime. Our new code fits not only broad band photometry but also spectral emission line flux. There is an option to fit observed SED with two templates with different physical properties. Our new code, PANHIT, is now in public, and was already applied to some high- z frontier galaxies.